Genetic markers in papillary bladder cancer - Dimopoulos, M.A.; Germenis, A.; Savides, P. (Journal d'Urologie, 1983)
The distribution of the phenotypes and the gene frequency of the 3rd fraction of complement (C3), the specific group (Gc), haptoglobin (Hp) and transferrin were studied in 133 patients with transitional cell cancer of the bladder (papillary cancer). Statistical analysis of these results, in comparison with the frequency of these genes in the general population, was unable to demonstrate a correlation between the distribution of these phenotypes and papillary cancer.